Dual Edge-Fed Left Hand and Right Hand Circularly Polarized Rectangular Micro-Strip Patch Antenna for Wireless Communication Applications - Prakasam, V.; Sandeep, P. (IRO Journal on Sustainable Wireless Systems, 2020)
Presently a days the remote correspondence framework advancement requires the ease, low profile, insignificant weight radio wire improvement which is cultivated of proceeding with incredible introduction finished a wide recurrence range. The MSPA architecture has facilitated this forward thinking skills trend. Within this paper work a 4.85 GHz circular polarization operating frequency is planned and simulated for RMSPA. The proposed antenna is capable of designing and inducing Left Hand Loop Polarization (LHCP) and Right Hand Loop Polarization (RHCP) using a cross-coupler that is directly attached to the micro-strip antenna to polarize the circular. The proposed paper work working recurrence is 4.85 GHz which is essentially utilized for satellite interchanges, full-time satellite TV organizations. This working recurrence is the IEEE 802.11a variation C band recurrence and this C band recurrence is utilized in Wi-Fi gadgets and Radio LAN. The proposed FR-4 roundabout polarization rectangular miniature strip fix radio wire is 1.6 mm thick. The proposed rectangular micro strip fix radio wire is planned and mimicked utilizing CSTMWS (Computer Simulation Technology Micro Wave Studio) programming. The full or working recurrence of proposed radio wire presents at 4.85 GHz for remote correspondences that gives S boundaries, data transmission and radiation example of Gain and directivity.
Keywords: Dual-fed; Micro Strip; Circular Polarization; FR-4; TV; LHCP; RHCP; CSTMWS; Gain; Bandwidth